PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA SKPD DINAS KOMUNIKASI DAN IFORMATIKA KABUPATEN MAROS - Nur'ani Nur'ani; Kherayani Nur; Ibriati Kartika Alimuddin (AkMen JURNAL ILMIAH, 2023)
The goal to be achieved in this study is to determine the effect of motivation and job satisfaction on the performance of the Aparatur Sipil Negara (ASN) at the SKPD Dinas Komunikasi dan Informatika Kabupaten Maros. The sample in this study was 58 Aparatur Sipil Negara (ASN) in the SKPD Dinas Komunikasi dan Informatika Kabupaten Maros. The data collection techniques used were literature review, interviews, and questionnaire distribution. The data analysis technique used is multiple linear regression. The hypothesis test consists of a t test (partial) and f test (simultan). The results of the study found that work motivation and job satisfaction have a positive and significant effect on performance. The results of this study also found that dominant motivation had a positive and significant effect on the performance of the Aparatur Sipil Negara (ASN) at the SKPD Dinas Komunikasi dan Informatika Kabupaten Maros